Anticancer platinum-drug delivered by mesenchymal stromal cells improves its activity on glioblastoma - Valentina Coccè; Eleonora Martegani; Luisa Doneda; Isabella Rimoldi; Giorgio Facchetti; Coffetti Giulia; Giorgio Lucchini; Leda Roncoroni; Aldo Giannì; Costantino Corradini; Giulio Alessandri; Emilio Ciusani; et al. (Cancer Nanotechnology, 2024)
Abstract Background Glioblastoma multiforme (GBM) is nowadays the most aggressive tumor affecting brain in adults with a very poor prognosis due to the limited therapies and the systemic cytotoxicity. Among the different new drugs, recently has been reported the in vitro anti-glioma activity of a new cationic platinum(II) complex bearing 8-aminoquinoline as chelating ligand (Pt-8AQ). The purpose of this research work was to confirm the activity of Pt-8AQ on U87-GM spheroid and to investigate the ability of Mesenchymal Stromal Cells (MSCs) to incorporate and release Pt-8AQ in its active form. The MSCs were primed with Pt-8AQ under optimized conditions and the secretome was analyzed for evaluating the cytotoxic activity of Pt-8AQ and the presence of Extracellular Vesicles (Evs). Results The principal results showed that Pt-8AQ incorporated by MSCs was released in the secretome and exerted a significant higher anticancer activity with respect to the free drug. The release of Pt-8AQ did not occur in Evs, as demonstrated for other drugs, but it could be delivered bound to some specific carriers able to enhance its bioavailability and efficacy. Some hypotheses are discussed to explain this surprisingly finding out that, however, it needs more investigations. Conclusions The major conclusions are that cell mediated drug delivery systems could provide a potential approach to facilitate the GBM therapy by intra-tumoral administration of cells loaded with Pt-8AQ, being MSCs able to integrate it into the tumor mass and exert high therapeutic efficacy in situ. The increased efficacy of Pt-8AQ delivered by MSCs even suggests to deeper investigate a possible direct use of MSCs secretome both in situ and/or by systemic administration, being secretome able to pass the blood–brain tumor.